Occurrence of Escherichia coli and faecal coliforms in drinking water at source and household point-of-use in Rohingya camps, Bangladesh - Zahid Hayat Mahmud (Gut Pathogens, 2019)
Abstract Background Safe water is essential for life but unsafe for human consumption if it is contaminated with pathogenic microorganisms. An acceptable quality of water supply (adequate, safe and accessible) must be ensured to all human beings for a healthy life. Methods We collected and analyzed a total of 12,650 drinking water samples, for the presence of Escherichia coli and faecal coliforms, from a large habitation of the displaced Rohingya population comprising of about 1.16 million people living within 4 km2. Results We found that 28% (n = 893) water samples derived from tubewells were contaminated with faecal coliforms and 10.5% (n = 333) were contaminated with E. coli; also, 73.96% (n = 4644) samples from stored household sources (at point of use—POU) were found contaminated with faecal coliforms while 34.7% (n = 2179) were contaminated with E. coli. It was observed that a higher percentage of POU samples fall in the highest risk category than that of their corresponding sources. Conclusions From our findings, it appears that secondary contamination could be a function of very high population density and could possibly occur during collection, transportation, and storage of water due to lack of knowledge of personal and domestic hygiene. Hence, awareness campaign is necessary, and the contaminated sources should be replaced. Further, the POU water should be treated by a suitable method.